GlyPh: a low-cost platform for phenotyping plant growth and water use - Pereyra Irujo, Gustavo Adrian (2012)
Breeding drought-tolerant crop varieties with higher water use efficiency could help maintain food supply to a growing population and save valuable water resources. Fast and accurate phenotyping is currently a bottleneck in the process towards attaining this goal, as available plant phenotyping platforms have an excessive cost for many research institutes or breeding companies. Here we describe a simple and low-cost, automatic platform for highthroughput measurement of plant water use and growth and present its utilisation to assess the drought tolerance of two soybean genotypes. The platform allows the evaluation of up to 120 plants growing in individual pots. A cart moving in only one direction carries the measuring and watering devices. Watering and measurement routines allow the simulation of multiple water regimes for each plant individually and indicate the timing of measurement of soil water content and image capture for growth estimation. Water use, growth and water use efficiency were measured in two experiments with different water scenarios. Differences in water use efficiency between genotypes were detected only in some treatments, emphasising the importance of phenotyping platforms to evaluate a genotype’s phenotype under a broad range of conditions in order to capture valuable differences, minimising the chance of artefacts and increasing precision of measurements.